The Effect of Weaning Food on the Body Weight of 6-12 Months Infants in Posyandu Kutoharjo Village, Kaliwungu, Kendal - Nahdloh, Nur; Priyantini M., Sri (Sains Medika : Jurnal Kedokteran dan Kesehatan, 2013)
According to Central Java Riskesdas in 2007 the severe malnutrition rate was 4.0%, while the rate in Kendal district was 3.1%. The age of 6-12 months is important because it is transition from liquid to solid foods. A purely breast milk diet is unsufficient to meet the nutritional needs of a fast growing baby growth. Weaning diet for baby is necessary to prevent growth disorder. The aim of the study was to assess the effect of weaning diet on weight gain of 6-12 month infant in posyandu (intergrated health center) of Kutoharjo Kaliwungu Kendal. The study was an analytic observational study with a cross sectional design. 87 samples were taken from the visits of children aged 6-12 months in the posyandu consisted of 53 boys and 34 girls who met the inclusion and exclusion criteria. The informations of weaning diet was obtained by questionare and interview. The results classified the baby into two groups namely the appropiate groups and inappropriate groups. The infant’s growth was assessed using the growth chart for the previous two months. Data were analyzed by Chi-Square Test. 51 (58.6%) infants fed of the appropriate solid foods, 44 (50.6%) had a good weight gain growth and only 7 (8%) infants has a bad weight gain. While of 36 (41.4%) infants fed inappropriate weaning diet, 30 (34.5%) infants had a bad weight gain and only 6 (6.9%) infants had a good weight gain. The Chi-Square analysis showed p-value of 0.000 (p<0.05), which means that there was a significant difference between the two groups. The weaning food affect on weight gain of 6-12 month infants in posyandu Kutoharjo village Kaliwungu Kendal.